2020
DOI: 10.1016/j.ajoc.2020.100857
|View full text |Cite
|
Sign up to set email alerts
|

Straylight due to intraocular lens opacification in a patient with asteroid hyalosis

Abstract: Purpose To report a rare case of intraocular lens (IOL) calcification in the presence of asteroid hyalosis with in-vivo measurements of straylight before and after treatment. Observations A patient with asteroid hyalosis presented with complaints of disability glare due to calcifications on the posterior surface of the IOL. Straylight, measured with the C-Quant, was 8.2x elevated compared to normal (log(s) 2.08). Dissolution of the posterior face IOL deposits was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…The ITSD algorithm detected higher glare angles in the pathological samples, which is consistent with the findings reported in the literature [ 40 , 41 ]. Results showed that the higher the amount of detected IS , the higher the computational costs for a successful restoration is ( Table 2 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The ITSD algorithm detected higher glare angles in the pathological samples, which is consistent with the findings reported in the literature [ 40 , 41 ]. Results showed that the higher the amount of detected IS , the higher the computational costs for a successful restoration is ( Table 2 ).…”
Section: Discussionsupporting
confidence: 91%
“…Considering the intraocular scattering as an important degradation factor, it is clear the increased IS in the presence of cataracts, lens opacifications, or even after cataract surgery [ 40 , 41 ]. However, retinal manifestations of systemic diseases such as diabetes mellitus can increase IS in a less clear way [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%